India’s Efforts towards Land Degradation and Desertification - Narain, Pratap (Annals of Arid Zone, 2016)
Natural resources of the country like land, water and forests are threatened due to demographic pressure, developmental activities and impacts of climate change. Intensive agriculture, particularly on fragile dryland ecosystems, may further aggravate land degradation. An unprecedented magnitude of degraded and waste lands in the country (120.72 Mha) is a cause of concern. It is broadly understood that about 50% of these lands can easily be afforested, while only one-third can be reclaimed and brought under cultivation with adoption of soil and water conservation measures.